Fear of humans as apex predators has landscape‐scale impacts from mountain lions to mice - Suraci, Justin P.; Clinchy, Michael; Zanette, Liana Y.; Wilmers, Christopher C.; Grether, Greg (Ecology letters, 2019)
Apex predators such as large carnivores can have cascading, landscape‐scale impacts across wildlife communities, which could result largely from the fear they inspire, although this has yet to be experimentally demonstrated. Humans have supplanted large carnivores as apex predators in many systems, and similarly pervasive impacts may now result from fear of the human ‘super predator’. We conducted a landscape‐scale playback experiment demonstrating that the sound of humans speaking generates a landscape of fear with pervasive effects across wildlife communities. Large carnivores avoided human voices and moved more cautiously when hearing humans, while medium‐sized carnivores became more elusive and reduced foraging. Small mammals evidently benefited, increasing habitat use and foraging. Thus, just the sound of a predator can have landscape‐scale effects at multiple trophic levels. Our results indicate that many of the globally observed impacts on wildlife attributed to anthropogenic activity may be explained by fear of humans.